When Does Status Turn Into Proactive Helping Behavior? The Moderating Role of Cooperative/Competitive Behavior Intention - Deng, Chuanjun; Liao, Shudi; Liu, Zhiqiang (Frontiers in Psychology, 2019)
Self-perceived status is considered an important antecedent of an employee’s extra-role behavior. However, the relationship between self-perceived status and “proactive helping” has been neglected in previous human resource management (HRM) research. Data were collected from 214 employees and their supervisors in two waves of dyads. The results indicated that self-perceived status is positively related to proactive helping behavior, while cooperative and competitive behavior intentions were both found to have a moderating effect on the relationship between self-perceived status and proactive helping behavior. Specifically, the relationship between self-perceived status and proactive helping behavior became stronger as the cooperative behavior intention increased, but weakened as competitive behavior intention increased. These conclusions indicate that organizations should guide employees to enhance their cooperative behavior intention or decrease their competitive behavior intention, which may increase their willingness to proactively help others. The study’s theoretical and practical contributions and future research are discussed.